Antioxidative Mechanism and Anisotropic Charge Transport Properties of Mangiferin: A Theoretical Study (Journal of Atomic and Molecular Sciences, 2018)
A quantum mechanical approach has been used to investigate the antioxidativemechanism for scavenging •OOH and •OH radicals using mangiferin in solutionphase. Mangiferin is also used as a potent applicant for organic semiconductor.The charge-transport properties in mangiferin have been studied based on thefirst-principle DFT combined with the Marcus-Hush theory. Density functional theory(DFT) calculations at the B3LYP/6-311+G(d,p) level were used to optimize mangiferinand its different forms. The lowest theoretical bond dissociation enthalpy (BDE) valuefor 7-OH site of mangiferin in water, indicates that 7-OH group is important in theantioxidant activity. The relative values of enthalpies also show that oxidation ofmangiferin by •OOH and •OH radical is an exothermic process. The predicted maximumelectron mobility value of mangiferin is 0.148 cm² $V^{-1} s^{-1},$ which appears atthe orientation angle near 49°/311° of conducting channel on the reference planes ab.Theoretical investigation of natural semiconductors is helpful for designing higherperformance electronic materials used in biochemical and industrial field to replaceexpensive and rare organic materials.
Keywords: anisotropic; organic semiconductor; mangiferin; antioxidant; charge transport.